2008
DOI: 10.1515/cclm.2008.096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress and inflammation in obese adults with metabolic syndrome

Abstract: High levels of free radicals together with low antioxidant capacity detected in obese adults indicate elevated oxidative stress, which is--together with systemic inflammation--further potentiated in the case of obese patients with metabolic syndrome. This imbalance in oxidative/antioxidative status and subclinical inflammatory state leads to higher risk of atherosclerotic and diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 36 publications
6
85
2
2
Order By: Relevance
“…Oxidative stress mediated by reactive oxygen species (ROS) and reactive nitrogen species has been detected in patients with MS (15,(17)(18)(19) and in obese patients, and ROS were correlated with serum NOx levels (15). In the present study, MS subjects also showed a significant increase in lipid hydroperoxides measured by chemiluminescence that correlated positively with NOx levels.…”
Section: Discussionsupporting
confidence: 53%
“…Oxidative stress mediated by reactive oxygen species (ROS) and reactive nitrogen species has been detected in patients with MS (15,(17)(18)(19) and in obese patients, and ROS were correlated with serum NOx levels (15). In the present study, MS subjects also showed a significant increase in lipid hydroperoxides measured by chemiluminescence that correlated positively with NOx levels.…”
Section: Discussionsupporting
confidence: 53%
“…This is in agreement with previous reports of increased MDA levels in patients with metabolic syndrome compared to controls. 9,[15][16][17] We observed a statistically significant lower FRAP levels in the study group when compared to controls (p=0.001). FRAP is a measure of the antioxidant power, based on the reduction of ferrous ions by the effect of the reducing power of plasma constituents, contributed by low molecular weight antioxidants of a hydrophilic and hydrophobic character especially vitamins C and E, serum bilirubin and serum uric acid.…”
Section: Introductionmentioning
confidence: 51%
“…7 Also, recently it has been found that there exists a racial difference in the levels of oxidative stress in patients with metabolic syndrome. 8 However, there are very few publications [9][10][11] which have studied the total antioxidant capacity as an index of antioxidant defense in patients with metabolic syndrome with conflicting results. The present study was thus taken up to evaluate the oxidative stress including total antioxidant status in patients with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is the principal factor in the development of the metabolic syndrome, due to that persons with obesity have deficient antioxidant defense and increased production of ROS [126,30,75], which leads to spoilage and subsequently cell death, resulting in tissue and organ damage, to tissues causing serious health problems such as insulin resistance [7], diabetes mellitus, and hypertension [82]. Moreover, in the metabolic syndrome, NAD(P)H oxidase, the major source of ROS in several tissues, is up-regulated, resulting in an increase of ROS production and the down-regulation of several antioxidant enzymes (SOD isoforms, GPx, and heme oxygenase) [114].…”
Section: Oxidative Stress and Diseasesmentioning
confidence: 99%